Analysis Of Student Learning Motivation In English Lessons In The Kurikulum Merdeka At UPTD SD Negeri 98 Barru - Achmad, Widya Karmila Sari; Nurhikmah, Nurhikmah; Usman, Hikmawati (Program Studi PGSD FIP UNM, 2024)
This study analyzes student learning motivation in English lessons at UPTD SD Negeri 98 Barru. The purpose of this study was to describe student learning motivation. The approach used in this research is a quantitative approach with a descriptive type of research. The population in this study were all fourth grade students of UPTD SD Negeri 98 Barru, while the sample was 20 people with Non Probability Sampling technique where the sampling used was purposive sampling which means that all members of the population will be sampled. The data sources in this study are teachers and students. Data collection techniques in the form of questionnaires and interviews. Data analysis techniques are descriptive statistics with percentage techniques. Based on the results of data analysis, student learning motivation in English lessons at UPTD SD Negeri 98 Barru is mostly in the high category and then in the medium category. It can be seen that the learning perseverance indicator has the highest frequency of the five indicators analyzed in this study.